Buloi Boyot pada Masyarakat Hukum Adat Desa Tungoi Satu Kecamatan Lolayan Kabupaten Bolaang Mongondow - Dewa Ezza Mahendra Ungko; Nirwan Junus; Dolot Alhasni Bakung (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study was to identify the factors that cause the existence of the case of buloi boyot or women who are pregnant out of wedlock without a valid marriage engagement in the Village Community Tungoi one Lolayan District Bolaang Mongondow. This study was conducted using descriptive analysis method with empirical juridical research. The subjects in this study were 3 (three) informants, namely; Village Head, Head of customary institutions and head of the Office of Religious Affairs. In this case the researchers used interview data, documentation and field observations. The results in this study indicate that the factors that cause related cases buloi boyot, such as; adolescent promiscuity less positive, lack of attention from parents, the influence of technology and information and lack of understanding of religion that has been believed. The efforts made by the village apparatus in handling the case by providing sanctions in the form of fines for the perpetrator based on written rules in Tungoi village regulation I Number 2 of 2022 concerning marriage customs. Although the rules have been implemented for the village community, in fact it is still not enough to accommodate and does not provide a deterrent effect at all. Therefore, the role of village heads and customary institutions has a great task to narrow or even eliminate such cases by conducting legal counseling and revising village regulations with more stringent sanctions so that local communities feel the deterrent effect